Analysis of adverse events in the elderly after acute myocardial infarction with reduced left ventricular ejection fraction. (2nd May 2022) - Oviedo Rodriguez, JD; Garcia Monsalvo, M; Alonso Fernandez De Gatta, M; Blanco Fernandez, F; Antunez Ballesteros, M; Bracho Bracchita, D; Cabanas Tendero, O; Elvira Laffond, A; Hernandez Martos, A; Hernandez Hidalgo, M; Rodriguez Estevez, L; Barreira De Sousa, G; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): Contract (CM19/00055) supported by the Instituto de Salud Carlos III in Spain (Co-funded by European Social Fund "Investing in your future"). Background: Elderly patients present higher risk for developing complications after an acute myocardial infarction (AMI) and reduced left ventricular ejection fraction (rLVEF) constitutes an adverse prognostic factor. Purpose: The main objective was to characterize elderly population with AMI and rLVEF and analyze prognostic factors. Methods: Retrospective analysis of hospitalized elderly patients (> 75 years old) with AMI and rLVEF <40% between January 2018 and December 2019. We analyze the occurrence of adverse outcomes in the follow-up: combined event (death from any cause and/or hospitalization from heart failure (HF) and/or AMI and/or ventricular arrhythmias) and its relationship with different variables (Figure 1). Results: Out of 179 patients, 100 >75 years old patients (55.9%) were included (Figure 1). After a mean follow-up of 3.8 [18.4] months, the combined event happened in 52% of them (figure 1, figure 2). Older age was associated with the combined event (86.8+8 years occurrence of event vs. 82.6+5.1 event-free, p=0.003). Variables significantly related with the occurrence of the combined event were chronic kidney disease (CKD) (72.7% occurrence of event vs. 46.2% event-free, p=0.032), higher values of creatinine (1.6+1 vs. 1.1+0.3, p=0.002), the presentation with acute pulmonary oedema (APO) (91.7% vs. 39.5%, p<0.001) and cardiogenic shock (93.2% vs. 41%, p<0.001), the need for noradrenaline (92.9% vs. 45.3%, p=0.001) and dobutamine (100% vs. 46.7%, p=0.001), the revascularization (completely percutaneous 43.5% of combined event, partial percutaneous 41.4%, partial surgical 100%, absence of revascularization 78.6%, p=0.034) and the presence of associated severe valvular disease (84.6% vs. 42%, p<0.001). We observed a trend although not statistically significant, to present higher values of NT-proBNP at the admission (16850 vs. 9044, p=0.71) and the initial presentation of non-ST elevation-acute coronary syndrome (NSTE-ACS) (28.6% of event in ST segment elevation myocardial infarction (STEMI) vs. 58.6% in NSTE-ACS, p=0.088) in patients who suffered the combined event in the follow-up. Conclusions: More than half the patients with 75 years old or higher presented adverse outcomes in the short term after a hospitalization for AMI with rLVEF. The most advanced age, the presentation as APO or cardiogenic shock, CKD, absence of revascularization, need for drugs and the presence of concomitant severe valvular disease were related with the appearance of the combined event (death, HF, AMI, ventricular arrhythmias).